Application of a concept development process to evaluate process layout designs using value stream mapping and simulation - Ki-Young Jeong (Journal of Industrial Engineering and Management, 2011)
Purpose: We propose and demonstrate a concept development process (CDP) as a framework to solve a value stream mapping (VSM) related process layout design optimization problem. Design/methodology/approach: A case study approach was used to demonstrate the effectiveness of CDP framework in a portable fire extinguisher manufacturing company. To facilitate the CDP application, we proposed the system coupling level index (SCLI) and simulation to evaluate the process layout design concepts. Findings: As part of the CDP framework application, three process layout design concepts - current layout (CL), express lane layout (ELL) and independent zone layout (IZL) - were generated. Then, the SCLI excluded CL and simulation selected IZL as the best concept. The simulation was also applied to optimize the performance of IZL in terms of the number of pallets. Based on this case study, we concluded that CDP framework worked well. Research limitations/implications: The process layout design optimization issue has not been well addressed in the VSM literature. We believe that this paper initiated the relevant discussion by showing the feasibility of CDP as a framework in this issue. Practical implications: The CDP and SCLI are very practice-oriented approaches in the sense that they do not require any complex analytical knowledge. Originality/value: We discussed a not well-addressed issue with a systematic framework. In addition, the SCLI presented was also unique.